Effectiveness of Dalbavancin Compared With Standard of Care for the Treatment of Osteomyelitis: A Real-world Analysis. (18th December 2021) - Cain, Alexander R; Bremmer, Derek N; Carr, Dustin R; Buchanan, Carley; Jacobs, Max; Walsh, Thomas L; Moffa, Matthew A; Shively, Nathan R; Trienski, Tamara L
Abstract: Background: Preliminary data suggest that the effectiveness of dalbavancin may be similar to current standard-of-care (SoC) treatment options for osteomyelitis with an advantageous dosing schedule. Methods: This was a retrospective, observational cohort study of adult patients diagnosed with osteomyelitis. Patients were matched 1:2 to dalbavancin (administered as 2 doses separated by 1 week) or SoC treatment for osteomyelitis according to the Charlson Comorbidity Index, site of infection, and causative pathogen. The primary objective was to determine the incidence of treatment failure after a 1-year follow-up period. Secondary objectives included hospital length of stay (LOS), infection-related 1-year readmission rates, and treatment-related adverse events. Results: A total of 132 patients received dalbavancin (n = 42) or SoC (n = 90). Baseline characteristics, including rates of surgical intervention, were similar between the 2 treatment groups. Treatment failure was similar between those who received dalbavancin and SoC (21.4% vs 23.3%; P = .81). Patients who received dalbavancin had a shorter hospital LOS (5.2 days vs 7.2 days; P = .01). There was no difference in the rates of infection-related readmission between the dalbavancin and the SoC group (31% vs 31.1%; P = .99). There were numerically fewer adverse events in the dalbavancin group compared with the SoC group (21.4% vs 36.7%; P = .08). Peripherally inserted central catheter line–related complications were reported in 17.8% of patients in the SoC group. Conclusions: Dalbavancin administered as a 2-dose regimen is a safe and effective option for the treatment of osteomyelitis.